A novel TRAPPC11 mutation in two Turkish families associated with cerebral atrophy, global retardation, scoliosis, achalasia and alacrima. Issue 3 (5th October 2016) - Koehler, Katrin; Milev, Miroslav P.; Prematilake, Keshika; Reschke, Felix; Kutzner, Susann; Jühlen, Ramona; Landgraf, Dana; Utine, Eda; Hazan, Filiz; Diniz, Gulden; Schuelke, Markus; Huebner, Angela; et al.
Abstract : Background: Triple A syndrome (MIM #231550) is associated with mutations in the AAAS gene. However, about 30% of patients with triple A syndrome symptoms but an unresolved diagnosis do not harbour mutations in AAAS . Objective: Search for novel genetic defects in families with a triple A-like phenotype in whom AAAS mutations are not detected. Methods: Genome-wide linkage analysis, whole-exome sequencing and functional analyses were used to discover and verify a novel genetic defect in two families with achalasia, alacrima, myopathy and further symptoms. Effect and pathogenicity of the mutation were verified by cell biological studies. Results: We identified a homozygous splice mutation in TRAPPC11 (c.1893+3A>G, [NM_021942.5], g.4:184, 607, 904A>G [hg19]) in four patients from two unrelated families leading to incomplete exon skipping and reduction in full-length mRNA levels. TRAPPC11 encodes for trafficking protein particle complex subunit 11 (TRAPPC11), a protein of the transport protein particle (TRAPP) complex. Western blot analysis revealed a dramatic decrease in full-length TRAPPC11 protein levels and hypoglycosylation of LAMP1. Trafficking experiments in patient fibroblasts revealed a delayed arrival of marker proteins in the Golgi and a delay in their release from the Golgi to the plasma membrane. Mutations in TRAPPC11 have previously been described to cause limb-girdle muscular dystrophy type 2S (MIM #615356). Indeed, muscle histology of our patients also revealed mild dystrophic changes. Immunohistochemically, β-sarcoglycan was absent from focal patches. Conclusions: The identified novel TRAPPC11 mutation represents an expansion of the myopathy phenotype described before and is characterised particularly by achalasia, alacrima, neurological and muscular phenotypes.